1995
DOI: 10.3102/00346543065003283
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Students and Classroom Interaction: An Overview and Critique

Abstract: The failure of U. S. schools to successfully educate Mexican American students has been well documented. In this article, studies of Mexican American students and classroom interaction are reviewed and critiqued from a Vygotskian perspective. Four traditional approaches to the study of Mexican American classroom interaction were found. The research reviewed suggests that teachers can better ensure Mexican American student involvement in classroom interaction through collaborative learning techniques, acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Davidson reports on a bilingual high school student who "often falls silent in integrated settings, not speaking unless spoken to" (p. 28). Research on Mexican American students in desegregated classrooms has noted that teachers created fewer opportunities for interaction and participation (Losey, 1995). Similar patterns are found in standard curriculum classrooms where L2 learners often find themselves excluded from classroom discourse (e.g., Biggs & Edwards, 1991;Harklau, 1999;Harper & Platt, 1998;Verplaetse, 2000).…”
Section: Discussionmentioning
confidence: 82%
“…Davidson reports on a bilingual high school student who "often falls silent in integrated settings, not speaking unless spoken to" (p. 28). Research on Mexican American students in desegregated classrooms has noted that teachers created fewer opportunities for interaction and participation (Losey, 1995). Similar patterns are found in standard curriculum classrooms where L2 learners often find themselves excluded from classroom discourse (e.g., Biggs & Edwards, 1991;Harklau, 1999;Harper & Platt, 1998;Verplaetse, 2000).…”
Section: Discussionmentioning
confidence: 82%
“…That is, all of the children in this investigation were living in poverty. The impact of poverty has been shown to be a far-reaching problem for children who are dual language learners (Losey, 1995) particularly if families have lived below the poverty threshold consistently rather than intermittently (Brooks-Gunn & Duncan, 1997;McLoyd, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Latin American immigrant youth in particular may have relationships with school adults that compromise their attachment to school. For example, studies have shown that teachers are less likely to praise and encourage Latino youth or to incorporate their ideas in class, as compared with youth of other ethnic backgrounds (Katz, 1999;Losey, 1995). Importantly, discrimination from teachers has been found to predict lower grades, academic self-concept and positive peer affiliation (Davison Aviles, Guerrero, Barajas Howarth, & Thomas, 1999).…”
Section: The Role Of Caring Adultsmentioning
confidence: 99%